Muscle Shear Elastic Modulus Provides an Indication of the Protection Conferred by the Repeated Bout Effect - Chalchat, Emeric; Siracusa, Julien; Bourrilhon, Cyprien; Charlot, Keyne; Martin, Vincent; Garcia-Vicencio, Sebastian (Frontiers in Physiology, 2022)
Background: The neuromuscular system is able to quickly adapt to exercise-induced muscle damage (EIMD), such that it is less affected by subsequent damaging exercise, a phenomenon known as the repeated bout effect (RBE). The objective was to determine whether the mechanical properties of the quadriceps, as evaluated by shear wave elastography (SWE), were less affected when a second bout of eccentric-biased exercise was performed 2 weeks later. It was hypothesized that the first bout would confer protection against extensive muscle damage through an adaptation of the muscle stiffness before the second bout (i.e., higher muscle stiffness). Methods: Sixteen males performed two identical bouts of downhill walking separated by 2 weeks (45 min at 4.5 km.h−1; gradient: 25%; load: 30% of the body mass). Rectus femoris (RF) and vastus lateralis (VL) resting shear elastic modulus (µ) and EIMD symptoms were measured before and up to 7 days following the exercise bouts. Changes in neuromuscular function was evaluated by maximal voluntary contraction torque, voluntary activation level, evoked mechanical response to single and double (10 and 100 Hz doublets) electrical stimulation. An index of protection (IP) was calculated for EIMD symptoms to assess magnitude the RBE. Results: EIMD symptoms were less affected after the second than the first exercise bout. RF and VL-µ increased (p < 0.001) only after the first exercise. RF µ was elevated up to 2 weeks after the end of the first exercise (p < 0.001) whereas VL µ was only increased up to 24 h. The increase in µ observed 2 weeks after the end of the first exercise was correlated with the IP; i.e., attenuation of alterations in muscle µ, 10 Hz-doublet amplitude and rate of torque development after the second exercise bout (p < 0.05). Conclusion: We showed that muscle µ assessed by SWE was sensitive to the RBE, with a differential effect between VL and RF. The persistent increase in µ was associated with the attenuation of neuromuscular impairments observed after the second bout, suggesting that the increased muscle stiffness could be a “protective” adaptation making muscles more resistant to the mechanical strain associated to eccentric contractions.